2018
DOI: 10.1186/s12966-018-0670-8
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sedentary behavior in preschoolers: a longitudinal assessment of trajectories and determinants

Abstract: BackgroundDespite physical activity (PA) being recognized as a critically important factor for good physical and mental health already early in life and throughout the life course, prospective data on activity behavior during the preschool years remains scarce. This study examined trajectories and determinants of levels and change in total PA (TPA), moderate-to-vigorous PA (MVPA) and sedentary behavior (SB) in a representative sample of Swiss preschoolers.MethodsData were drawn from the Swiss Preschoolers’ Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
47
1
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 57 publications
14
47
1
7
Order By: Relevance
“…Accelerometer data revealed that children engaged in less than half an hour of MVPA and almost 8 hours of SB per day in our sample, indicating a sedentary lifestyle at a young age in Singapore. Compared with our findings, studies in the USA, 34 Canada 35 and Australia 36 showed that preschool-aged children spent much more time in MVPA and less in SB. Although research among early childhood is limited in Asia, similarly low levels of PA and high levels of SB were objectively measured and reported in Japanese preschoolers.…”
Section: Discussioncontrasting
confidence: 96%
“…Accelerometer data revealed that children engaged in less than half an hour of MVPA and almost 8 hours of SB per day in our sample, indicating a sedentary lifestyle at a young age in Singapore. Compared with our findings, studies in the USA, 34 Canada 35 and Australia 36 showed that preschool-aged children spent much more time in MVPA and less in SB. Although research among early childhood is limited in Asia, similarly low levels of PA and high levels of SB were objectively measured and reported in Japanese preschoolers.…”
Section: Discussioncontrasting
confidence: 96%
“…Most children in this study were measured when they were younger than 5y and hence we may have missed this transition, because we found that sedentary time decreased with advancing age in both ethnic groups, and levels of MVPA and vector magnitude CPM increased. This spike in MVPA (which precedes an age-related decline throughout the life-course [42]) has been reported previously and is often attributed to young children mastering movement skills [43,44]. We observed that older white British children performed more light physical activity than younger white British children, but there were no such differences in South Asian children.…”
Section: Patterns Of Sedentary Time and Physical Activitysupporting
confidence: 79%
“…There is evidence that lower amounts of time spent being sedentary are also associated with improved physical and psychological health among children and adolescents, but it is unclear if these associations are independent of physical activity [3,4]. Physical activity levels change with age, increasing between ages 3 and 6, and appearing to peak around the age that children start school (approximately age 6) while sedentary time is relatively stable in this age range [5]. However, several studies have shown that physical activity declines and sedentary time increases in an approximately linear fashion between ages 6 and 15, with girls less active than boys across all age groups [6,7].…”
Section: Introductionmentioning
confidence: 99%